A zirconium-gadolinium alloy with concentrated nitric acid corrosion resistance and neutron shielding effect

Through the design method based on the cluster linking atomic model, the phase composition of zirconium gadolinium alloy is simplified and the components are adjusted, which solves the problems of insufficient nitric acid corrosion resistance and neutron shielding effects in spent fuel post-treatment, and achieves efficient design and excellent performance.

CN115050501BActive Publication Date: 2025-04-25XIAN RARE METAL MATERIALS RES INST CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210413876.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-20
Publication Date
2025-04-25
Estimated Expiration
2042-04-20

AI Technical Summary

Technical Problem

The existing zirconium alloys have problems with nitric acid corrosion resistance and insufficient neutron shielding effects in spent fuel post-treatment.

Method used

Based on the cluster linking atomic model, the composition of zirconium gadolinium alloy is designed to simplify the phase composition, obtain a double cluster model, and by adjusting the content of Zr atoms, a zirconium gadolinium alloy with excellent nitric acid corrosion resistance and neutron shielding effect is designed.

Benefits of technology

The design efficiency of zirconium gadolinium alloy is improved, the experimental trial and error process is reduced, time and resource waste is avoided, and a zirconium gadolinium alloy with excellent corrosion resistance of concentrated nitric acid and neutron shielding effect is obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115050501B_ABST
    Figure CN115050501B_ABST
Patent Text Reader

Abstract

The present invention discloses a zirconium-gadolinium alloy with strong corrosion resistance and neutron shielding effect. Firstly, the composition of the zirconium-gadolinium alloy is designed based on the cluster plus linked atomic model, and the bcc-Zr phase is simplified to a cluster formula [Zr-Zr 14 ]Zr, simplifying the hcp‑Zr phase into a cluster form [Zr‑Zr 12 ]Zr3, obtain a double cluster model, then design to dissolve Gd into the hcp-Zr phase, obtain the basic composition formula of the zirconium-gadolinium alloy, on this basis, increase the content of Zr atoms in sequence, continue to design to obtain the adjusted composition formula of the zirconium-gadolinium alloy, and then successively mix, smelt and process to obtain the zirconium-gadolinium alloy with concentrated nitric acid corrosion resistance and neutron shielding effect. The present invention improves the design efficiency of the zirconium-gadolinium alloy, reduces unnecessary experimental trial and error processes, avoids time and resource waste, obtains the zirconium-gadolinium alloy with excellent concentrated nitric acid corrosion resistance and neutron shielding effect, and simplifies the preparation process of the zirconium-gadolinium alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of alloy design and nuclear materials, and in particular relates to a zirconium-gadolinium alloy with concentrated nitric acid corrosion resistance and neutron shielding effect. Background Art

[0002] The importance of nuclear chemical safety is self-evident. Among them, the problems of corrosion and neutron radiation faced by spent fuel reprocessing equipment have always been a difficult problem that plagues the design of key equipment. Neutrons can cause great harm to both equipment and operators. The use of super-corrosion-resistant alloy materials with neutron absorption properties to manufacture related equipment and instruments has become a reliable solution to alleviate and ensure the safety of nuclear chemical industry, ensuring that the related equipment has high operating reliability in high temperature, high radiation, and boiling nitric acid. In the international post-processing equipment, Russia, Britain, Germany and other countries use stainless steel, the United States and Japan use titanium alloys, France uses optimized zirconium alloys, and my country currently uses corrosion-resistant titanium alloys. The Sino-French joint large-scale commercial reprocessing-recycling plant project has a designed reprocessing capacity of 800 tons / year, and plans to adopt the French solution (a certain type of zirconium alloy). In addition, the development of spent fuel dry storage containers, spent fuel transport containers, dissolvers, evaporators and other equipment also has a very large demand for neutron absorption materials.

[0003] At present, the research on zirconium alloys for spent fuel reprocessing is mainly focused on industrial pure zirconium (Zr-702) and Zr-704, Zr-705, Zr-2, Zr-4, etc. These alloys are proven excellent nitric acid corrosion-resistant materials with amazing corrosion resistance. The corrosion rate is less than 0.00125mm / year. The source of corrosion resistance is the super corrosion-resistant ZrO2 film generated on the surface of the zirconium alloy. When dynamic nuclear waste impacts, wears, and scratches the zirconium alloy container, the oxide film can self-repair.

[0004] Commonly used neutron absorbing materials are mainly alloy materials containing boron (B) or gadolinium (Gd). 10 The neutron absorption cross section of B is 3837b. Due to its low cost, it is often used as a neutron absorption additive element for nuclear reactor spent fuel storage. However, gadolinium (Gd) is more effective than boron (B) as an alloy additive for neutron absorption: (1) Natural gadolinium has two extremely high cross-section absorption isotopes 155 Gd- (60600b), 157 Gd- (139000b), the neutron absorption cross section is significantly higher than 10 B (3837b), and is therefore an excellent neutron absorbing material; (2) During the degradation of alloy materials under long-term corrosion conditions, the degradation rate of Gd-containing components in water is lower than that of CrB. Therefore, it is very attractive to use corrosion-resistant alloys containing gadolinium (Gd) to store, transport and dispose of spent nuclear fuel.

[0005] Theoretically, Gd cannot be dissolved in large quantities in conventional metal alloy systems. Except for α-Zr, which can dissolve up to 2.8 at.% Gd, other alloy systems, such as Ti, 316L, and Cr, can hardly dissolve Gd. This provides a new idea for the design of my country's second-generation spent fuel reprocessing structural materials.

[0006] Designing a new type of nitric acid corrosion-resistant alloy component with neutron poisoning effect, mastering the design principle of the new zirconium alloy from the material gene, and using the cluster plus linked atomic model to guide the design of the new zirconium alloy has high use value. Summary of the invention

[0007] The technical problem to be solved by the present invention is to provide a zirconium-gadolinium alloy with concentrated nitric acid corrosion resistance and neutron shielding effect in view of the deficiencies of the above-mentioned prior art. The present invention designs the composition of the zirconium-gadolinium alloy based on the cluster plus linked atomic model, simplifies the phase composition of the zirconium-gadolinium alloy to obtain a double cluster model, and obtains the basic composition formula and adjusted composition formula of the zirconium-gadolinium alloy based on this, thereby improving the design efficiency of the zirconium-gadolinium alloy, reducing unnecessary experimental trial and error processes, avoiding time and resource waste, and obtaining a zirconium-gadolinium alloy with excellent concentrated nitric acid corrosion resistance and neutron shielding effect.

[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is: a zirconium-gadolinium alloy with concentrated nitric acid corrosion resistance and neutron shielding effect, characterized in that the zirconium-gadolinium alloy composition is firstly designed based on the cluster plus linked atomic model, and the bcc-Zr phase is simplified to a cluster formula [Zr-Zr 14 ]Zr, simplifying the hcp-Zr phase into a cluster type [Zr-Zr 12 ]Zr3, and then the double cluster model is designed to dissolve Gd into the hcp-Zr phase. Based on the fact that less than one Gd atom can be dissolved in the cluster plus linked atom model of the hcp-Zr phase, the basic composition formula of the zirconium-gadolinium alloy is obtained according to the double cluster model: [Gd-Zr 12 ]Zr3+[Zr-Zr 14 ]Zr=Gd1Zr 31 ≈Gd 3.13 Zr 96.87 On this basis, the content of Zr atoms is increased successively, and the adjusted composition formula of the zirconium-gadolinium alloy is further designed. Then, based on the atomic percentage corresponding to the basic composition formula or the adjusted composition formula of the zirconium-gadolinium alloy, the ingredients are mixed, smelted and processed in sequence to obtain the zirconium-gadolinium alloy with concentrated nitric acid corrosion resistance and neutron shielding effect.

[0009] Cluster plus linked atomic model has corresponding models for different metal crystal structures such as fcc, bcc, hcp, etc. Usually, the structure of cluster plus linked atomic model is as follows Figure 1As shown, it includes cluster units and connecting atoms distributed between the cluster units, and the cluster unit is composed of a cluster central atom and cluster shell atoms surrounding the cluster central atom.

[0010] The zirconium-gadolinium alloy of the present invention has zirconium as the main component and gadolinium as the added component; pure metal zirconium can obtain different phases according to different phase transition temperatures and processing techniques, and bcc-Zr phase and hcp-Zr phase are the main phases in the low temperature region. The present invention designs and constructs the zirconium-gadolinium alloy based on the phase structure of pure metal zirconium, designs the composition of the zirconium-gadolinium alloy based on the cluster plus linked atomic model, firstly simplifies the bcc-Zr phase and hcp-Zr phase in the zirconium-gadolinium alloy into a cluster formula, and obtains a double cluster model, such as Figure 2 As shown, the basic composition formula of the Gd-Zr solid solution is obtained; since each atom in the cluster plus linked atomic model will occupy the most reasonable position according to its own quantity and characteristics when combined, each atom will occupy the most "comfortable" position. When the quantity is just right and meets the cluster formula requirements, the best performance of the corresponding alloy in a certain aspect, that is, the basic composition formula obtained by the zirconium-gadolinium alloy cluster formula is often only close to the optimal composition but not the optimal composition. Therefore, on the basis of the basic composition formula of the zirconium-gadolinium alloy, the present invention increases the content of Zr atoms in sequence, adjusts the number of Zr atoms as connecting atoms, so as to reasonably connect the corresponding cluster formulas, and continues to design the adjusted composition formula of the zirconium-gadolinium alloy; finally, the present invention uses the atomic percentage corresponding to the basic composition formula or the adjusted composition formula of the zirconium-gadolinium alloy as the basis, and sequentially obtains the zirconium-gadolinium alloy with concentrated nitric acid corrosion resistance and neutron shielding effect through batching, smelting and processing.

[0011] The present invention designs the composition of the zirconium-gadolinium alloy based on the cluster plus linked atomic model, improves the design efficiency of the zirconium-gadolinium alloy, reduces unnecessary experimental trial and error processes, avoids waste of time and resources, obtains the zirconium-gadolinium alloy with excellent concentrated nitric acid corrosion resistance and neutron shielding effect, and thus improves the research and development speed of the zirconium-gadolinium alloy.

[0012] The above-mentioned zirconium-gadolinium alloy with concentrated nitric acid corrosion resistance and neutron shielding effect is characterized in that the adjusted composition formula of the zirconium-gadolinium alloy includes: Gd1Zr 33 ≈Gd 2.94 Zr 97.06 , Gd1Zr 35 ≈Gd 2.78 Zr 97.22 , Gd1Zr 47 ≈Gd 2.08 Zr 97.92 , Gd1Zr 63 ≈Gd 1.56 Zr 98.44. The present invention is based on the cluster plus linking atom model, and by increasing the content of Zr atoms, the adjusted composition formula of the above-mentioned zirconium-gadolinium alloy is obtained. Because Zr is the main solvent element and accounts for the majority, the maximum solid solubility is determined based on the proportion of solute atoms contained in the stable Zr-Gd cluster structure, but the number of solute atoms (i.e., colloid atoms or linking atoms, glue atoms) that serve as the connection between clusters cannot be determined immediately, and it is necessary to expand on the basic composition formula to lock in the optimal number of linking atoms.

[0013] The above-mentioned zirconium-gadolinium alloy with concentrated nitric acid corrosion resistance and neutron shielding effect is characterized in that the mass percentage of the zirconium-gadolinium alloy corresponding to the basic composition formula and the adjusted composition formula is in the range of Gd 1~13 Zr 87~99 , the atomic percentage range is Gd 0.58~7.98 Zr 92.02~99.42 The present invention comprehensively considers the inhomogeneity and component segregation factors of the zirconium-gadolinium alloy caused by the process in the actual industrial production of the zirconium-gadolinium alloy, and determines the mass percentage and atomic percentage range of the zirconium-gadolinium alloy, which is more in line with the requirements of actual industrial production and has higher practical value.

[0014] Compared with the prior art, the present invention has the following advantages:

[0015] 1. The present invention designs the composition of the zirconium-gadolinium alloy based on the cluster plus linked atomic model, simplifies the phase composition of the zirconium-gadolinium alloy to obtain a double cluster model, and uses this as a basis to obtain the basic composition formula and the adjusted composition formula of the zirconium-gadolinium alloy, thereby improving the design efficiency of the zirconium-gadolinium alloy, reducing unnecessary experimental trial and error processes, avoiding waste of time and resources, and obtaining a zirconium-gadolinium alloy with excellent concentrated nitric acid corrosion resistance and neutron shielding effect.

[0016] 2. The present invention focuses on the Zr-Gd binary phase diagram and solid solubility limit, reasonably predicts the content range and adjusts the number of Zr atoms to obtain a series of zirconium-gadolinium alloy composition formulas, thereby obtaining a zirconium-gadolinium alloy with excellent concentrated nitric acid corrosion resistance and neutron shielding effect.

[0017] 3. The zirconium-gadolinium alloy of the present invention has simple components and is easy to prepare and smelt, thus simplifying the preparation process of the zirconium-gadolinium alloy of the present invention.

[0018] 4. The zirconium-gadolinium alloy of the present invention has a reasonable composition design and thus has excellent resistance to nitric acid and neutron poisoning.

[0019] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a simplified two-dimensional schematic diagram of the cluster-linked atomic model of the present invention.

[0021] Figure 2 For the present invention [Zr-Zr 14 ]Zr and [Zr-Zr 12 ]Schematic diagram of the cluster structure in the Zr3 double cluster model.

[0022] Figure 3 This is a comparison chart of the corrosion rates of the zirconium-gadolinium alloy of Example 2 of the present invention and the titanium-gadolinium alloy of Comparative Example 1 after 24 hours and 48 hours.

[0023] Figure 4 This is a diagram showing the absorption effect of zirconium-gadolinium alloys of Examples 1 to 5 of the present invention on thermal neutrons. DETAILED DESCRIPTION

[0024] Example 1

[0025] The composition formula of the zirconium-gadolinium alloy of this embodiment, which is resistant to concentrated nitric acid corrosion and has a neutron shielding effect, is Gd1Zr 31 , mass percentage is Gd 5.27 Zr 94.72 , atomic percentage is Gd 3.13 Zr 96.87 Based on the atomic percentage and taking into account the loss factors of each element in subsequent processing such as smelting, high-purity metal materials of zirconium and gadolinium in corresponding proportions are prepared and mixed, and smelted more than three times by a smelting method such as consumable or non-consumable arc melting, suspension melting, ultra-gravity melting, powder metallurgy, electron beam or laser beam melting to obtain a uniform zirconium-gadolinium alloy ingot, and the zirconium-gadolinium alloy ingot is successively subjected to heat treatment, forging, machining, hot and cold rolling, etc. to obtain a zirconium-gadolinium alloy profile.

[0026] Example 2

[0027] The composition formula of the zirconium-gadolinium alloy of this embodiment, which is resistant to concentrated nitric acid corrosion and has a neutron shielding effect, is Gd1Zr 33 , mass percentage is Gd 4.96 Zr 95.04 , atomic percentage is Gd 2.94 Zr 97.06 Based on the atomic percentage and taking into account the loss factors of each element in subsequent processing such as smelting, high-purity metal materials of zirconium and gadolinium in corresponding proportions are prepared and mixed, and smelted more than three times by a smelting method such as consumable or non-consumable arc melting, suspension melting, ultra-gravity melting, powder metallurgy, electron beam or laser beam melting to obtain a uniform zirconium-gadolinium alloy ingot, and the zirconium-gadolinium alloy ingot is successively subjected to heat treatment, forging, machining, hot and cold rolling, etc. to obtain a zirconium-gadolinium alloy profile.

[0028] Comparative Example 1

[0029] The titanium-gadolinium alloy of this comparative example is obtained by adding 3% by mass of Gd element to the titanium-tantalum alloy Ti35; the titanium-tantalum alloy Ti35 contains 5.5% to 6.5% by mass of Ta and trace elements, and the rest is Ti.

[0030] Figure 3 This is a comparison chart of the corrosion rates of the zirconium-gadolinium alloy of Example 2 of the present invention and the titanium-gadolinium alloy of Comparative Example 1 after 24 hours and 48 hours, Figure 3 Gd1Zr 33 -1 and Gd1Zr 33 -2 is the same parallel sample, from Figure 3 It can be seen that compared with the titanium-gadolinium alloy prepared in Comparative Example 1 by adding 3% Gd to the titanium-tantalum alloy Ti35, the main structural material of spent fuel reprocessing, to improve its neutron absorption capacity, the zirconium-gadolinium alloy designed based on the cluster plus linked atomic model of the present invention has better resistance to nitric acid corrosion.

[0031] Example 3

[0032] The composition formula of the zirconium-gadolinium alloy of this embodiment, which is resistant to concentrated nitric acid corrosion and has a neutron shielding effect, is Gd1Zr 35 , mass percentage is Gd 4.69 Zr 95.31 , atomic percentage is Gd 2.78 Zr 97.22 Based on the atomic percentage and taking into account the loss factors of each element in subsequent processing such as smelting, high-purity metal materials of zirconium and gadolinium in corresponding proportions are prepared and mixed, and smelted more than three times by a smelting method such as consumable or non-consumable arc melting, suspension melting, ultra-gravity melting, powder metallurgy, electron beam / laser beam melting, etc. to obtain a uniform zirconium-gadolinium alloy ingot, and the zirconium-gadolinium alloy ingot is successively subjected to heat treatment, forging, machining, hot and cold rolling, etc. to obtain a zirconium-gadolinium alloy profile.

[0033] Example 4

[0034] The composition formula of the zirconium-gadolinium alloy of this embodiment, which is resistant to concentrated nitric acid corrosion and has a neutron shielding effect, is Gd1Zr 47 , mass percentage is Gd 3.54 Zr 96.46 , atomic percentage is Gd 2.08 Zr 97.92 Based on the atomic percentage and taking into account the loss factors of each element in subsequent processing such as smelting, high-purity metal materials of zirconium and gadolinium in corresponding proportions are prepared and mixed, and smelted more than three times by a smelting method such as consumable or non-consumable arc melting, suspension melting, ultra-gravity melting, powder metallurgy, electron beam / laser beam melting, etc. to obtain a uniform zirconium-gadolinium alloy ingot, and the zirconium-gadolinium alloy ingot is successively subjected to heat treatment, forging, machining, hot and cold rolling, etc. to obtain a zirconium-gadolinium alloy profile.

[0035] Example 5

[0036] The composition formula of the zirconium-gadolinium alloy of this embodiment, which is resistant to concentrated nitric acid corrosion and has a neutron shielding effect, is Gd1Zr 63 , mass percentage is Gd 2.66 Zr 97.34 , atomic percentage is Gd 1.56 Zr 98.44 Based on the atomic percentage and taking into account the loss factors of each element in subsequent processing such as smelting, high-purity metal materials of zirconium and gadolinium in corresponding proportions are prepared and mixed, and smelted more than three times by a smelting method such as consumable or non-consumable arc melting, suspension melting, ultra-gravity melting, powder metallurgy, electron beam / laser beam melting, etc. to obtain a uniform zirconium-gadolinium alloy ingot, and the zirconium-gadolinium alloy ingot is successively subjected to heat treatment, forging, machining, hot and cold rolling, etc. to obtain a zirconium-gadolinium alloy profile.

[0037] Figure 4 Figure 2 is a graph showing the absorption of thermal neutrons by zirconium-gadolinium alloys according to Examples 1 to 5 of the present invention. Figure 4 It can be seen that the zirconium-gadolinium alloy designed based on the cluster plus linked atomic model of the present invention has excellent neutron absorption performance.

[0038] Example 6

[0039] The zirconium-gadolinium alloy of this embodiment which is resistant to concentrated nitric acid corrosion and has a neutron shielding effect is in an unsaturated state of Gd atoms, and the mass percentage is Gd1Zr 99 , atomic percentage is Gd 0.58 Zr 99.42 Based on the atomic percentage and taking into account the loss factors of each element in subsequent processing such as smelting, high-purity metal materials of zirconium and gadolinium in corresponding proportions are prepared and mixed, and smelted more than three times by a smelting method such as consumable or non-consumable arc melting, suspension melting, ultra-gravity melting, powder metallurgy, electron beam or laser beam melting to obtain a uniform zirconium-gadolinium alloy ingot, and the zirconium-gadolinium alloy ingot is successively subjected to heat treatment, forging, machining, hot and cold rolling, etc. to obtain a zirconium-gadolinium alloy profile.

[0040] Example 7

[0041] The zirconium-gadolinium alloy of this embodiment, which is resistant to concentrated nitric acid corrosion and has a neutron shielding effect, is in a supersaturated state of Gd atoms, with a mass percentage of Gd 13 Zr 87 , atomic percentage is Gd 7.98 Zr 92.02Based on the atomic percentage and taking into account the loss factors of each element in subsequent processing such as smelting, high-purity metal materials of zirconium and gadolinium in corresponding proportions are prepared and mixed, and smelted more than three times by a smelting method such as consumable or non-consumable arc melting, suspension melting, ultra-gravity melting, powder metallurgy, electron beam or laser beam melting to obtain a uniform zirconium-gadolinium alloy ingot, and the zirconium-gadolinium alloy ingot is successively subjected to heat treatment, forging, machining, hot and cold rolling, etc. to obtain a zirconium-gadolinium alloy profile.

[0042] The zirconium-gadolinium alloy profiles prepared in Examples 1 to 7 were tested, and their nitric acid corrosion resistance, neutron shielding performance, and mechanical properties were evaluated. The zirconium-gadolinium alloy profiles that passed the test and evaluation were used to manufacture structural components for nuclear fuel reprocessing.

[0043] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A zirconium-gadolinium alloy having concentrated nitric acid corrosion resistance and neutron shielding effect, characterized in that: Firstly, the composition of the zirconium-gadolinium alloy was designed based on the cluster plus linked atomic model, and the bcc-Zr phase was simplified to the cluster formula [Zr-Zr 14 ]Zr, simplifying the hcp-Zr phase into a cluster type [Zr-Zr 12 ]Zr3, and then the double cluster model is designed to dissolve Gd into the hcp-Zr phase. Based on the fact that less than one Gd atom can be dissolved in the cluster plus linked atom model of the hcp-Zr phase, the basic composition formula of the zirconium-gadolinium alloy is obtained according to the double cluster model: [Gd-Zr 12 ]Zr3+[Zr-Zr 14 ]Zr=Gd1Zr 31 ≈Gd 3.13 Zr 96.87 On this basis, the content of Zr atoms is increased successively, and the adjusted composition formula of the zirconium-gadolinium alloy is further designed. Then, based on the atomic percentage corresponding to the basic composition formula or the adjusted composition formula of the zirconium-gadolinium alloy, the ingredients are mixed, smelted and processed in sequence to obtain the zirconium-gadolinium alloy with concentrated nitric acid corrosion resistance and neutron shielding effect.

2. The zirconium-gadolinium alloy having concentrated nitric acid corrosion resistance and neutron shielding effect according to claim 1, characterized in that: The adjusted composition formula of the zirconium-gadolinium alloy includes: Gd1Zr 33 ≈Gd 2.94 Zr 97.06 , Gd1Zr 35 ≈Gd 2.78 Zr 97.22 , Gd1Zr 47 ≈Gd 2.08 Zr 97.92 , Gd1Zr 63 ≈Gd 1.56 Zr 98.44 .

3. The zirconium-gadolinium alloy having concentrated nitric acid corrosion resistance and neutron shielding effect according to claim 1, characterized in that: The mass percentage of the zirconium-gadolinium alloy corresponding to the basic composition formula and the adjusted composition formula is in the range of Gd 1~13 Zr 87~99 , the atomic percentage range is Gd 0.58~7.98 Zr 92.02~99.42 .

Citation Information

Patent Citations

  • Corrosion-resistant and high-neutron-absorption-performance gadolinium-zirconium alloy foil and preparation method

    CN110643876A

  • Fuel element for nuclear reactor

    JP2000298187A